The Role Of Higher Education Leaders In Improving Students' English Language Skills - Harianta Sembiring (SEAN Institute, 2024)
English language skills are now mandatory for students to master. Because English is an international language, it will be an asset in competing. Higher Education Leaders are figures who are responsible and essential in improving students' English language skills. This research aims to see and examine how university leaders play a role in improving students' English language skills—a type of descriptive qualitative research. Data collection uses interview, observation, and documentation methods. The research uses stages of data reduction, data presentation, and data verification. The research results show that university leaders play a role in improving students' English language skills. Higher education leaders act as educators, managers, leaders, and motivators. Four stages are carried out to improve students' English language skills: the training stage, habituation stage, development stage, and learning stage. To improve students' English language skills, higher education leaders are the determinants of success whether students have good and competent English language skills.